Pembinaan Keagamaan Siswa-Siswi Sekolah Menengah Atas melalui Rohani Islam (Rohis) di Kota Samarinda dan Balikpapan - Tahir, M.; Amirullah, Amirullah (IAIN Samarinda, 2019)
The aim of this paper is to explain the concept of religious mentoring by Rohani Islam (Rohis) in planting Islamic religious values to high school students in Samarinda and Balikpapan. This research applies qualitative technique in analyzing data collected trhough in-depth interviews, documentations, and observations. Findings of this research reveal that Rohis’ programs pertaining to increasing the students’ observance of religion (Islam) are based on routine schedule such as daily, weekly, monthly, and annual programs. All of Rohis’ programs represent the implementation of five aspects of religious dimensions; faith, religious practices, religious experiences, religious consequences, and religious knowledge. Rohis’ programs of religious mentoring to high schools students can be categorised into Dakwah Ammah (general proselytizing) and Dakwah Khashshah (special proselytizing). Keywords: Dakwah ammah and khashshah, Rohis, and students religious mentoring